Digital Transformation's Impact on the Sports Tourism Industry: Opportunities and Challenges (Tạp chí khoa học Đào tạo và Huấn luyện Thể thao, 2024)
Digital Transformation's Impact on the Sports Tourism Industry: Opportunities and Challenges